2006
DOI: 10.1017/s0952523806231055
|View full text |Cite
|
Sign up to set email alerts
|

Radial motion bias in macaque frontal eye field

Abstract: The visual responsiveness and spatial tuning of frontal eye field~FEF! neurons were determined using a delayed memory saccade task. Neurons with visual responses were then tested for direction selectivity using moving random dot patterns centered in the visual receptive field. The preferred axis of motion showed a significant tendency to be aligned with the receptive-field location so as to favor motion toward or away from the center of gaze. Centrifugal outward! motion was preferred over centripetal motion. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…Under this condition, few of the visual neurons were modulated at all and those that were did so well after SSRT. The fact that in this study some of the visual neurons responded to the replacement of the target by a distractor in their receptive field before TSRT is consistent with reports that some FEF neurons can signal stimulus features in the search array (e.g., Bichot et al 1996;Peng et al 2008;Xiao et al 2006).…”
Section: Visual Response To the Target Stepsupporting
confidence: 91%
“…Under this condition, few of the visual neurons were modulated at all and those that were did so well after SSRT. The fact that in this study some of the visual neurons responded to the replacement of the target by a distractor in their receptive field before TSRT is consistent with reports that some FEF neurons can signal stimulus features in the search array (e.g., Bichot et al 1996;Peng et al 2008;Xiao et al 2006).…”
Section: Visual Response To the Target Stepsupporting
confidence: 91%
“…For example, single-unit recordings have shown that the FEF contains both visual and perisaccadic neurons. Visual neurons have activity that is closely linked to the onset of visual stimuli (2,(8)(9)(10), whereas perisaccadic neurons have activity that is restricted to the time immediately around the execution of saccades (2,22,23). Some measurements suggest that these cell types are discrete classes of neurons, rather than ends of a continuum (11).…”
Section: Discussionmentioning
confidence: 99%
“…Single-unit recordings have shown that a substantial fraction of FEF neurons have little or no perisaccadic activity and instead have strong, short-latency visual responses (2). These visually driven neurons can respond selectivity to different stimulus dimensions (8,9) and distinguish the behavioral relevance of stimuli in an array (10). The activity of these neurons, unlike FEF neurons with perisaccadic activity, is strongly correlated with stimulus onset and only weakly correlated with the timing of saccadic responses (11).…”
mentioning
confidence: 99%
“…Favoring this hypothesis, it has been reported that FEF neurons are active during attentive tracking (Xiao et al, 2007) and that microstimulation of the FEF produces changes in the RF profile of V4 neurons (Armstrong et al, 2006). The small differences between the magnitude of the effects in outward and inward trials may relate to biases in eye movement planning toward concentrically and eccentrically moving targets (Segraves et al, 1987;Xiao et al, 2006). One issue to be addressed by future studies is whether changes in the RF or movement field profiles of FEF neurons precede the expansion of MT RFs described in our study.…”
Section: Origins Of the Modulatory Signalmentioning
confidence: 99%